(untitled) (Pedagogical Horizons, 2024)
Using the University College of Education of the Diocese of Linz as an example, this article shows how professional theoretical knowledge from the areas of psychotherapy and supervision at an institution is transferred into the training of teachers and implemented there to guide action with a view to holistic personality development, professionalization and professional identity formation. The aim is to document a historical development in outline and to present existing concepts argumentatively and with reference to relevant positions. In an outlook, possibilities for a differentiated further development of existing concepts as well as desiderata for accompanying evaluative research are discussed.